Implementasi Akad Tabaru Pada Asuransi Syariah Guna Meningkatkan Perekonomian - Putri Dwi Setyowati; Alfina Khoirun Nisa; Agus Eko Sujianto (Jurnal Publikasi Ekonomi dan Akuntansi, 2023)
ABSTRACT, The development of Islamic financial institutions in Indonesia has experienced quite rapid development. Islamic financial institutions have many kinds, one of which is Islamic insurance. As insurance labeled sharia, it is obligatory in its operations to comply with Islamic principles and values. This research was conducted to analyze how the implementation of the tabarru contract on Islamic insurance in order to improve the economy. This research method uses a qualitative approach with the method of analysis of literature studies or library research. The data used in this research comes from books, journals, scientific papers, to legal online searches. The results of this study indicate that the implementation of the tabarru contract in Islamic financial institutions with a research focus on Islamic insurance institutions has implemented the tabarru contract in its activities. As well as having an indirect positive impact on improving the economy.